Philosophy of the basic education curriculum implications for gender-sensitive education - Callueng, Eva Aurora D. (2007)
The relevant elements of the current educational framework for the Basic Education Curriculum (BEC) to show that it is lacking in pursuing a holistic and gender-sensitive approach to education was examined in this paper. Document analysis and key respondent interviews were done to identify some possible errors involved in the application of the philosophy behind the current BEC. Participant observation method and focus group discussions were also utilized. It was found that the current BEC is inadequate in terms of mandating when homosexuality as a concept will be introduced in formal education. Also, evidence showed that teachers are found to be unaware of Gender and Development Program. Having a gender-sensitive society that recognizes equal rights among all persons regardless of any classification is believed to be attainable if the findings of this research will be addressed soon.